CHARACTERISTICS OF LATGALIAN POPULAR MUSIC (2005–2016) - Gusāns, Ingars (Via Latgalica, 2017)
Looking at the events of the last decade in the life of Latgalian popular music, there may be twofold feelings; one will feel that in the field of popular music life is in full swing; another will feel that everything is stunted and hopeless. The purpose of the research is to describe the situation of Latgalian popular music (success, problems) between 2005 and 2016. The object of the research is Latgalian groups and performers. In the given study, the concept of the popular Latgalian music is presented, which includes pop music, rock music, jazz, rap, and other styles of popular music that may involve folk elements, as well as shlager music performed in the Latgalian language, as well as its authors (preferably) have a kinship with Latgale and who (preferably) have released at least one album where at least one song (preferably not a folk song) is in Latgalian, and even if it is a folk song, then in a less traditional arrangement. The following resources are used: correspondence with musicians, Internet resources, author’s own observations as a listener and as a musician. In Latgale musical tendencies keep up with the times and, this is also confirmed by one of the few music reviewers who mentions Latgalian music, Sandris Vanzovičs, here (in Latgale) virtually all the music styles of the world are represented, all niches are filled (Gusāns 2015: 1). Latgalian popular music has high quality ethno-rock artists – „Laimas muzykanti”, poprock group „Bez PVN”, „Dabasu Durovys”, specific rap group „Borowa MC”, strong rock and metal performers „Green Novice” and Sovvaļnīks, and a representative of ethno jazz Biruta Ozoliņa. Also in the last few years an interesting alternative stage has been created represented by the group „Kapļi” and „Jezups i Muosys”. Between 2005 and 2016 at least 39 albums of Latgalian popular music have been released. The most successful style for Latgalian performers („Galaktika”, „Ginc un Es”, Inga un Normunds, „Baltie Lāči”, „Patrioti. Ig”, „Dricānu Dominante”, etc.) was and still is the shlager music style, where several performers are still active and gaining success in the main criterion of Latvian music evaluation - in different song polls. The list of successes for pop and rock musicians is not so long, also taking into account the differences in the rating system, usually only the winner is emphasized; therefore, getting on the list of the five nominees for the given prize is highly appreciated. The biggest problem in Latgale and also in Latvian music is the decline of the music market. The greatest potential for loss and success is the introduction of new technologies, which make the majority of listeners choose to play music on their phone or computer, resulting in the loss of significance of music recorded in CDs. Artists are now trying to distribute music through the Internet, where much is determined by chance for the group to be noticed among other amounts of information and thus begins to symbolically earn on the sale of recordings on the Internet, but very often there are situations where high quality performances and lovely songs are left unnoticed. Thus, it is also musicians' own responsibility for the originality of the material being placed on the Internet, both in musical, textual and visual form, to promote visibility. The second biggest problem is the decrease in the audience that affects musicians in several ways: a) the decrease of the number of people, including the Latgalian audience (emigration), makes the sale of CDs meaningless; the lack of purchasers; b) the decrease of population also has an effect on the concerts and festivals; c) not only a part of the public, but also talented musicians emigrate in relation to the economic situation. Also, the third problem of Latgalian popular music is very topical; it is the place of Latgalian culture in the Latvian media, here it is worth noting the intolerance of the Latvian media, especially the strongest broadcasting stations (with a few exceptions over a decade) against songs performed in Latgalian. Therefore, Latgalian groups can rarely present their musical compositions elsewhere in Latvia, as a result of which many performers write songs in Latvian, not in Latgalian. It is necessary to emphasize that in recent years musicians („Dabasu Durovys”, „Green Novice”, etc.) pay more attention to the written language and its consistent use in published texts and song titles unless it is presented as a stylistic, specific feature of the group. Thus group texts can be mentioned as worth considering for people who want to learn or get in touch with Latgalian texts. Acquiring a place on the Latvian music market depends on many factors – recognizable, high quality song, successful management, solid concert performance, and elaborate group image and, above all, the idea of why it is being done.